Teias de reciprocidade entre educadores de artes de Goiânia e a comunidade de Ribeirão de Areia (MG) - Inácio, Elmira Vicente (2016)
This work called "reciprocity Webs: between Goiânia Arts Educators and Ribeirão community of Sand (MG)" presents a narrative about the experiences of educational practices and pedagogical mediations processes that occurred from daily life and rites of a rural community in the State of Minas Gerais. The theoretical north of this work is critical pedagogy and cultural pedagogy that punctuate the role of producers of knowledge that position themselves in processo of change sociocultural. The research is of documentary character since it was carried out through the analysis of interviews, image files (photographs and audiovisual) and through reflection on the pedagogical processes triggered by interaction with that community. The research considered the experiences in the course of training activities that promoted theoretical and practical discussions about Popular Culture and Art which culminated in the (re) invention of organized visual methods and mediated by Goiânia arts educators. The survey results point to the perception of the importance of collaborative processes in the formation of educators, adolescents and youth art education in non-formal space that elaborate socio-cultural and environmental projects in the community guided experiences. relational webs intrinsically change our educational practices.